IMPLEMENTATION OF PETSHOP LOCATION BASED SERVICE (LBS) MAPPING IN MEDAN USING ANDROID SMARTPHONES - Ricky Ramadhan Harahap; Barany Fachri (INFOKUM, 2022)
Technological developments are increasing rapidly, where people need information quickly and precisely, especially in geographic information systems. The absence of media for the community to find a location makes it difficult for the community to find a place, especially the PetShop Store in the city of Medan. The community needs information about the geographic location of the Petshop store in Medan City digitally so that the public can more easily find the location and information about the Petshop store. Realizing that technological developments are growing, technology developers are creating an Android-based mobile application to make it easier for people to find the location of a Petshop store in Medan City. Android is an open source mobile operating system that makes it easier for application developers to create and develop these applications with Google Map as their digital map. With the geographic information system application for the location of the Petshop store in Medan City based on android, the community can easily find the location of the eiger store in Medan City along with information about prices and facilities available at the eiger store in Medan City.